THE EXISTENCE OF MAQASHID SYARIAH PRINCIPLES ON FINTECH ISLAMIC SECURITIES CROWDFUNDING (I-SCF) - Ocktavia, Annisa Kartika; Al-Ayubi, Solahudin; Herman, Sebastian (Al-Infaq: Jurnal Ekonomi Islam, 2024)
This research aims to analyze Islamic Securities Crowdfunding (I-SCF) at PT Shafiq Digital Indonesia (SHAFIQ) with Maqashid Syariah approach. Methodology Thisresearch uses a qualitative descriptive research method to examine the application of maqosid sharia principles at PT Shafiq Digital Indonesia. This research utilizes literature study with Maqashid Syariah perspective as the main reference. The results showed that PT Shafiq Digital Indonesia has applied maqosid sharia principles in the development of ISCF fintech. It can be seen from the various contracts contained in PT Shafiq Digital Indonesia's transactions. The limitations of this research are limited to the I-SCF of PT Shafiq Digital Indonesia. So that further research can conduct further research on I-SCF in other companies and even countries for comparison purposes. This research also only analyzes several contracts in PT. Shafiq Digital Indonesia transactions so that future research can use other contracts in accordance with the development of the SHAFIQ platform. This research is important so that Muslims can keep up with the flow of technological developments and fintech financial institutions in accordance with the maqashid sharia corridor. Maqashid sharia study on I-SCF shows that practically I-SCF is a financial instrument that can encourage economic growth and community welfare.